2019
DOI: 10.1111/and.13347
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using tadalafil 5 mg/day on neutrophil–lymphocyte and platelet–lymphocyte ratios in mild‐medium and severe erectile dysfunction patients; and comparison of clinical response

Abstract: To examine the relation between NLR (neutrophil–lymphocyte ratio) and PLR (platelet–lymphocyte ratio) rates and the severity of ED (erectile dysfunction) and the effect of tadalafil 5 mg/day on these, a total of 143 patients were retrospectively evaluated. Sixty‐three patients with ED who came for follow‐up examinations in the 1st month of the treatment were included as the study group, and 80 men who were not diagnosed with ED were as the control group. The age and Charlson Comorbidity Indexes (CCI) of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Findings associated with this result are also different in other studies. Porst et al (2014) observed higher improvement following daily tadalafil administration in patients with mild ED, whereas Demirci & Ozgur (2019) observed higher recovery rates in severe ED patients. On the other hand, Suetomi et al (2008) observed that both baseline and post-treatment IIEF scores were inversely correlated with an increase in the number of MetS components.…”
Section: Discussionmentioning
confidence: 94%
“…Findings associated with this result are also different in other studies. Porst et al (2014) observed higher improvement following daily tadalafil administration in patients with mild ED, whereas Demirci & Ozgur (2019) observed higher recovery rates in severe ED patients. On the other hand, Suetomi et al (2008) observed that both baseline and post-treatment IIEF scores were inversely correlated with an increase in the number of MetS components.…”
Section: Discussionmentioning
confidence: 94%
“…In the study by Demirci & Ozgur (2019), the NLR increased with ED severity: in patients with mild‐moderate ED ( n = 30), the mean value was 1.83 compared to patients with severe ED ( n = 33) who had a mean NLR of 1.93.…”
Section: Discussionmentioning
confidence: 94%
“…We chose this cut‐off of NLR ≥ 3 versus <3 because it is very close to the mean value and has been used in previous studies analysing the influence of NLR on ED. Demirci and Ozgur (2019) showed a significant inverse correlation between the NLR and the IIEF‐5 score. Ventimiglia et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Then, 11 studies with full text were further reviewed for eligibility of our meta-analysis, excluding 27 records for unrelating to our topic. Eventually, 7 studies were remained for our meta-analysis, meeting the predefined inclusion criteria (Akbas et al, 2016;Aslan et al, 2019;Demirci & Ozgur, 2019;Demirci et al, 2020;Erdogan et al, 2020;Liao et al, 2021;Sambel et al, 2018). Among the 7 eligible studies, a total of 929 ED patients and 737 healthy controls were included in our meta-analysis.…”
Section: Search Results and Basic Characteristics Of Included Studiesmentioning
confidence: 99%